When gas analysis assists with postmortem imaging to diagnose causes of death. (June 2015) - Varlet, V.; Smith, F.; Giuliani, N.; Egger, C.; Rinaldi, A.; Dominguez, A.; Chevallier, C.; Bruguier, C.; Augsburger, M.; Mangin, P.; Grabherr, S.
Graphical abstract: Highlights: We used forensic imaging tools to investigate gaseous volumes in bodies. We used analytical chemistry tools to investigate their chemical compositions. Reliable gaseous indicators were determined to document the context of death. Gas analysis allows to differentiate alteration cases and gaseous embolisms. Gas analysis allows to distinguish the different stages of body alteration. Abstract: Postmortem imaging consists in the non-invasive examination of bodies using medical imaging techniques. However, gas volume quantification and the interpretation of the gas collection results from cadavers remain difficult. We used whole-body postmortem multi-detector computed tomography (MDCT) followed by a full autopsy or external examination to detect the gaseous volumes in bodies. Gases were sampled from cardiac cavities, and the sample compositions were analyzed by headspace gas chromatography–mass spectrometry/thermal conductivity detection (HS-GC–MS/TCD). Three categories were defined according to the presumed origin of the gas: alteration/putrefaction, high-magnitude vital gas embolism (e.g., from scuba diving accident) and gas embolism of lower magnitude (e.g., following a traumatic injury). Cadaveric alteration gas was diagnosed even if only one gas from among hydrogen, hydrogen sulfide or methane was detected. In alteration cases, the carbon dioxide/nitrogen ratio was often >0.2, except in the case of advanced alteration, when methane presence was the best indicator. In the gas embolism cases (vital or not), hydrogen, hydrogen sulfide and methane were absent. Moreover, with high-magnitude vital gas embolisms, carbon dioxide content was >20%, and the carbon dioxide/nitrogen ratio was >0.2. With gas embolisms of lower magnitude (gas presence consecutive to a traumatic injury), carbon dioxide content was <20% and the carbon dioxide/nitrogen ratio was often <0.2. We found that gas analysis provided useful assistance to the postmortem imaging diagnosis of causes of death. Based on the quantifications of gaseous cardiac samples, reliable indicators were determined to document causes of death. MDCT examination of the body must be performed as quickly as possible, as does gas sampling, to avoid generating any artifactual alteration gases. Because of cardiac gas composition analysis, it is possible to distinguish alteration gases and gas embolisms of different magnitudes.